Analysing factors influencing purchase intentions, perception and culture for consumers of women’s luxury footwear in South Africa - Bridglall, Shenai (School of Management Studies, 2019)
Consumer behaviour and purchase intention are some of the most discussed topics in marketing academia and practice alike. A rich and constantly developing body of literature complements this field. However, even though many theories exist, one’s understanding remains limited in some areas. The motivation for conducting this study was attributable to the researcher’s experience who has worked with luxury footwear brands in South Africa, Europe and Asia. In addition, marketers’ failure to understand consumer buying behaviour and purchase intentions are difficult tasks that have driven the researcher to undertake this study. The primary objective was to determine the factors that influenced the purchase intentions of consumers of luxury footwear This study explored South Africa and the literature around propositions of the model of purchase intentions proposed by Vigneron and Johnson through a positivist lens. Data was collected using Elle South Africa’s Instagram social media networking platform. A total of 1350 participants were involved in the survey, which was only limited to Cape Town and Johannesburg. Only 200 participants met the criteria of women spending money on luxury footwear. Non-probability convenience sampling technique was used in this study because the sample elements were readily available using the Elle South Africa Instagram social networking platform. Quantitative data was analysed through Structural Equation Modelling and the findings were presented in frequency tables. The results showed that culture moderated the relationships between luxury perception and the purchase intention for consumers of luxury women’s footwear; extrinsic factors were more relevant than intrinsic factors in the purchasing of luxury footwear; and that luxury perception positively influences the purchase intentions for consumers of the luxury footwear market in South Africa. Knowing what motivates women’s purchase intentions is critical to growing brand customer bases, which is possible through improving market segmentation. Suggestions for improving segmentation are possible through greater definition of variables. Additional research was suggested to establish details which encourage this market to buy luxury footwear brands. This is particularly important in terms of South Africa, which is home to many different cultures where these ethnic groups are confined to a small region. Customers need to be able to make trade-offs between intrinsic and extrinsic factors and costs in this market, which is critical knowledge especially in economic downturns.